Using context clues in determining contextual meaning of Arabic words - Abdul Jabar, Mohd Azidan; Mansor, Syazmira (Universiti Putra Malaysiara Press, 2021)
Language context plays an important role in determining the meaning of a word. To understand its meaning, it is imperative that context be considered. Today, many students have difficulty understanding the meaning of Arabic words as they are unable to understand the context. However, words, phrases or sentences in a text can serve as a guide or clue to understand the meaning of unknown words. This is termed as context clues. This study aims to identify how context clues help students determine the contextual meaning of an Arabic word. Their understanding process is analysed from the critical discourse analysis perspective using a three-dimensional model introduced by Fairclough (1989). This study was conducted using a questionnaire and interviews with twenty undergraduates studying Arabic language from five Malaysian universities. Five Arabic words were selected from five news texts quoted from the Arab news portal al-Ra’i (http://alrai.com/); covering sports, economics, politics, social and technology. The words selected have many meanings, depending on the context of the sentence. Students must determine the meaning contextually by stating the context clues in the text that guided them. The findings show that context clues can help students understand the meaning of Arabic words and enhance their understanding based on its sentence context.